Short communicationImmediate improvement of left internal thoracic artery graft flow after subclavian artery stenting - Ertem, Ahmet Goktug; Kilic, Harun; Arslantas, Ugur; Yeter, Ekrem (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
We report a case of treatment of subclavian-coronary steal syndrome with stenting and immediate improvement of left internal mammalian artery flow